A new species of Arostrilepis from Ellobius tancrei (Rodentia: Cricetidae) in Mongolia. Issue 6 (15th May 2022) - Dursahinhan, Altangerel T.; Brooks, Daniel R.; Botero-Cañola, Sebastian; Gardner, Scott L.
Abstract: Abstract: Cestodes of the genus Arostrilepis Mas-Coma and Tenora 1997 have a Holarctic distribution with 16 species occurring among 28 species of mostly arvicoline hosts. The type species of the genus is Arostrilepis horrida (von Linstow, 1901), described initially as Taenia horrida von Linstow, 1901, from murine rodents in Lower Saxony (Niedersachsen), Germany. Here we report the first helminth parasite from the mole-vole, Ellobius tancrei, in Mongolia which is the first subterranean rodent known to be infected with Arostrilepis in the Palearctic. In addition, we describe a new species: Arostrilepis batsaikhani n. sp. which most closely resembles A. microtis Gulyaev and Chechulin 1997, differing from this species with a genetic distance of about 4% (using cytochrome-b) and by having distinctly large cirrus spines, testes that are larger and fill the whole segment measured anterior–posterior and larger eggs.